Bionic design for anticoagulant surface via synthesized biological macromolecules with heparin-like chains1. Issue 71 (2nd August 2015) - Ran, Fen; Song, Haiming; Wu, Jiayu; Ma, Lang; Niu, Xiaoqin; Fan, Huili; Kang, Long; Zhao, Changsheng
<x xml:space="preserve">Abstract</x> A heparin-like anticoagulant membrane surface with functional groups and conjugated structure was constructed by blending a synthesized copolymer for blood purification.